Polyolefin material as well as preparation method and application thereof
By adding quaternary ammonium salt-coated hemp fibers to polyolefin materials, the problems of existing materials being easily bitten and lacking antibacterial and flame retardant properties are solved, and the multiple performance improvements of the materials are achieved, which are suitable for the application of farm facilities.
Patent Information
- Application Number
- CN202411839741.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
Existing polyolefin materials are easily chewed by animals in farms, have short service life and lack antibacterial and flame retardant properties.
By adding hemp fibers and quaternary ammonium salts to the polyolefin material, the quaternary ammonium salts are coated on the surface of the hemp fibers to improve the mechanical properties, antibacterial properties and flame retardancy of the material.
It has achieved good mechanical properties, anti-bite properties, antibacterial properties and flame retardancy of polyolefin materials, and is suitable for the preparation of animal farm facilities.
Smart Images

Figure BDA0005187671710000011 
Figure BDA0005187671710000091 
Figure BDA0005187671710000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a polyolefin material and a preparation method and application thereof. Background Art
[0002] In order to achieve factory-based and intensive development, the breeding industry has seen a rapid increase in scale breeding, such as pig and bamboo rat breeding. Farms in the livestock industry are becoming more and more common. Farm construction requires a variety of polymer plastic materials, among which polyolefin mats used in floor systems are easily bitten / arched by animals, have a short service life, have no antibacterial function, and are prone to cause animals to be infected with bacteria; and are flammable, with a high risk of fire. Therefore, it is necessary to develop a polyolefin material that is anti-biting, antibacterial and flame retardant. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present application is to provide a polyolefin material and a preparation method and application thereof, wherein the polyolefin material has good anti-bite properties, antibacterial properties and flame retardancy.
[0004] In order to achieve the above objectives, in a first aspect, the present application provides a polyolefin material comprising the following components in parts by weight:
[0005]
[0006] Adding hemp fiber to polyolefin materials is beneficial to improving its mechanical properties, such as rigidity (such as bending modulus), hardness, etc., making it less likely to be chewed, and is also beneficial to improving its antibacterial properties; quaternary ammonium salts have antibacterial properties, and coating them on the surface of hemp fibers can not only improve the antibacterial properties of the materials, but also avoid hemp fiber agglomeration, so that the hemp fibers can better play a role in improving the mechanical properties and antibacterial properties of the materials. At the same time, quaternary ammonium salts are prone to produce hydrogen halides at high temperatures, which can cooperate with flame retardants to improve the flame retardancy of the materials.
[0007] The polyolefin material also has good mechanical properties, anti-bite properties, antibacterial properties and flame retardancy, and is suitable for preparing animal farm facilities, such as mats for floor systems.
[0008] Preferably, the weight percentage of quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber is 9% to 51%. The weight percentage of quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber can be selected as 9%, 10%, 20%, 30%, 40%, 50%, 51% or a range formed by any two of the above values.
[0009] More preferably, the weight percentage of quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber is 23% to 31%.
[0010] When the weight percentage of the quaternary ammonium salt in the quaternary ammonium salt-coated hemp fiber is 9% to 51%, especially in the range of 23% to 31%, the quaternary ammonium salt can not only exert its antibacterial function, but also better exert its hemp fiber stiffness enhancement effect, thereby avoiding weakening of the hemp fiber stiffness enhancement effect due to excessive quaternary ammonium salt.
[0011] The weight percentage of the quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber can be measured based on an inductively coupled plasma mass spectrometry (ICP-AES) testing method. For example, 8 mL of concentrated nitric acid (HNO3 content of about 68 wt%, commercially available) and 2 mL of hydrogen peroxide (H2O2 content of about 30 wt%, commercially available) are mixed and dispersed to obtain a mixed solution, 0.2 g of the quaternary ammonium salt coated hemp fiber sample is weighed and placed in the mixed solution, microwave digestion is performed at 50° C. for 1 h, and then the volume is fixed to 50 mL with distilled water to obtain a sample solution to be tested, and then the halogen element concentration in the sample solution to be tested is tested by ICP-AES, and then the corresponding weight percentage of the quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber is calculated. The weight percentage of the quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber can be calculated according to the following formula:
[0012] y=(50C×10 -6 ) / (0.2x)×100,
[0013] Wherein, y is the weight percentage of quaternary ammonium salt in quaternary ammonium salt coated hemp fiber, %;
[0014] C is the concentration of halogen element in the sample solution to be tested, mg / L;
[0015] x is the content of halogen element in quaternary ammonium salt, g / g.
[0016] Preferably, the average length of the flax fibers in the quaternary ammonium salt coated flax fibers is ≥1 mm, and the average diameter is ≤100 μm. The average length of the flax fibers in the quaternary ammonium salt coated flax fibers can be selected as 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm or a range formed by any two of the above values; the average diameter can be selected as 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range formed by any two of the above values.
[0017] More preferably, the average length of the quaternary ammonium salt coated ramie fibers is 1 to 4 mm, and the average diameter of the quaternary ammonium salt coated ramie fibers is 5 to 95 μm.
[0018] When the average length of the hemp fibers in the quaternary ammonium salt-coated hemp fibers is ≥1 mm and the average diameter is ≤100 μm, especially when the average length is 1 to 4 mm and the average diameter is 5 to 95 μm, it is more conducive to improving the material's anti-bite properties, antibacterial properties and mechanical properties, such as hardness, bending modulus, etc.
[0019] The average length and average diameter of the quaternary ammonium salt coated hemp fiber are detected by a two-dimensional measuring method, which is as follows: 200 quaternary ammonium salt coated hemp fibers are randomly selected, their diameters and lengths are counted respectively, and then the average values are calculated to obtain the average length and average diameter.
[0020] Preferably, the method for preparing the quaternary ammonium salt coated hemp fiber comprises soaking the hemp fiber in an alkali solution, washing with water and performing a steam explosion treatment.
[0021] Preferably, the alkali content in the alkali solution is 0.5-10 wt %, the soaking temperature in the alkali solution is 1-90° C., and the soaking time in the alkali solution is 0.5-24 h. As an example, the alkali in the alkali solution includes at least one of sodium hydroxide and potassium hydroxide.
[0022] Preferably, the quaternary ammonium salt content in the quaternary ammonium salt solution is 30-60wt%, the soaking temperature in the quaternary ammonium salt solution is 1-90°C, and the soaking time in the alkali solution is 0.5-48h. As an example, the quaternary ammonium salt in the quaternary ammonium salt solution includes at least one of didecyl dimethyl ammonium bromide, didecyl dimethyl ammonium chloride, dioctyl dimethyl ammonium bromide, and dioctyl dimethyl ammonium chloride.
[0023] Preferably, the number of steam explosions is 1 to 5 times, and the pressure of each steam explosion is 0.5 to 10 MPa.
[0024] Preferably, the hemp fiber in the quaternary ammonium salt coated hemp fiber includes at least one of ramie fiber, flax fiber and sisal fiber.
[0025] Preferably, the method for preparing the quaternary ammonium salt coated hemp fiber comprises soaking or ultrasonically treating the hemp fiber with a quaternary ammonium salt solution.
[0026] Preferably, the quaternary ammonium salt in the quaternary ammonium salt-coated bast fiber includes at least one of didecyldimethylammonium bromide, didecyldimethylammonium chloride, dioctyldimethylammonium bromide and dioctyldimethylammonium chloride.
[0027] Preferably, the polyolefin resin includes at least one of high-density polyethylene, low-density polyethylene, linear low-density polyethylene, and polypropylene. More preferably, the polyolefin resin is polypropylene. The polypropylene resin can be selected from at least one of copolymer polypropylene and homopolymer polypropylene.
[0028] Preferably, the melt flow rate of the polyolefin resin at 230°C / 2.16kg is 0.1 to 100 g / 10min. For example, the melt flow rate of the polyolefin resin at 230°C / 2.16kg is 0.1 g / 10min, 1 g / 10min, 3 g / 10min, 5 g / 10min, 1 g / 10min, 20 g / 10min, 30 g / 10min, 40 g / 10min, 50 g / 10min, 60 g / 10min, 70 g / 10min, 80 g / 10min, 90 g / 10min or 100 g / 10min.
[0029] More preferably, the polyolefin resin has a melt flow rate of 1 to 60 g / 10 min at 230° C. / 2.16 kg.
[0030] The melt flow rate of the polyolefin resin is measured according to ASTM D1238-13 "Test method for melt flow rate of thermoplastics using an extrusion plastometer".
[0031] Preferably, the compatibilizer comprises a polar monomer graft polymer, wherein the polymer comprises at least one of ethylene-vinyl acetate copolymer and ethylene-ethyl acrylate copolymer, and the polar monomer comprises maleic anhydride or a derivative thereof.
[0032] The above-mentioned monomer grafted polymer acts as a compatibilizer, which can improve the interfacial compatibility between hemp fiber and polyolefin, enhance the mechanical properties of the material, such as rigidity and hardness, and enhance the material's anti-bite property; and the acidity in the contained polymer and the polar monomer is superimposed to stimulate the animal's olfactory receptors and enhance the material's anti-bite property.
[0033] Preferably, the hypophosphite flame retardant includes at least one of aluminum hypophosphite and divinyl aluminum hypophosphite. The hypophosphite flame retardant is acidic and can stimulate the sense of smell of animals, produce an avoidance effect, and further improve the anti-bite performance of the material.
[0034] Preferably, the following components are also included in weight: 0.1-1 part of antioxidant and 0.1-1 part of lubricant.
[0035] Preferably, the antioxidant includes at least one of a phenolic antioxidant, a phosphite antioxidant, a divalent sulfur antioxidant, and a hindered amine antioxidant.
[0036] Preferably, the lubricant includes at least one of an amide lubricant, a metal soap lubricant, and a low molecular ester lubricant, wherein the low molecular ester lubricant refers to a lower alcohol ester formed by a fatty acid, and the carbon number of the fatty acid generally does not exceed 20.
[0037] Preferably, the mass fraction of the polyolefin resin in the polyolefin material is above 20%, such as 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or a range formed by any two of the above values.
[0038] Without impairing the technical effect of the present application, additives such as color powder and weathering agent can be added to the polyolefin material. For example, the weathering agent can be selected from at least one of benzophenone, benzotriazole and hindered amine.
[0039] In a second aspect, the present application also provides a method for preparing the polyolefin material, which comprises the following steps: mixing all component raw materials, melt-extruding, granulating, and drying to obtain the polyolefin material.
[0040] Preferably, the melt extrusion is carried out in a twin-screw extruder. The aspect ratio of the twin-screw extruder is preferably (36-48): 1. The temperature of each zone of the twin-screw extruder is preferably set as follows: 80-120°C in zone 1, 180-200°C in zones 2-5, and 200-210°C in zones 6-8.
[0041] In a third aspect, the present application provides the use of the polyolefin material in animal farm facilities. For example, the polyolefin material can be used to prepare mats for animal farm floor systems.
[0042] Compared with the prior art, the beneficial effects of this application are:
[0043] (1) The polyolefin material of the present application improves its mechanical properties and antibacterial properties and enhances its anti-bite performance by adding hemp fibers; the flame retardant properties of the material are improved by adding hypophosphite flame retardants, and the hypophosphite flame retardants are acidic, which can stimulate the sense of smell of animals, produce an avoidance effect, and enhance the anti-bite performance of the material; coating hemp fibers with quaternary ammonium salts can not only utilize the antibacterial properties of the quaternary ammonium salts themselves to improve the antibacterial properties of the material, but also avoid hemp fiber agglomeration, which is beneficial to the hemp fibers to improve the mechanical properties and antibacterial properties of the material. At the same time, quaternary ammonium salts are easy to produce hydrogen halides at high temperatures, which can cooperate with hypophosphite flame retardants to improve the flame retardancy of the material.
[0044] (2) The polyolefin material of the present application has good mechanical properties, anti-bite properties, antibacterial properties and flame retardancy, and is suitable for preparing animal farm facilities, such as mats for floor systems. DETAILED DESCRIPTION
[0045] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0046] The raw materials used in the following examples and comparative examples are shown in Table 1, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind.
[0047] PP 1: Copolymer PP, melt index at 230℃ / 2.16kg is 3g / 10min, Sino-Korea Petrochemical, K8003;
[0048] PP 2: copolymer PP, melt index at 230℃ / 2.16kg is 9g / 10min, CNOOC Shell, EP300M;
[0049] PP 3: Copolymer PP, melt index at 230℃ / 2.16kg is 98g / 10min, Sinochem Refining, EP640V;
[0050] Quaternary ammonium salt coated hemp fiber 1: average diameter of 15 μm, average length of 3.4 mm, quaternary ammonium salt weight percentage of 26%, the preparation method is as follows: commercially available bundled ramie long fiber with an average diameter of 200 μm is uniformly cut into 4 mm long short fibers, then placed in a 2wt% NaOH solution at 25°C for 8 hours, washed with clean water several times to remove the residual sodium hydroxide, and the washed short fibers are placed in a 50wt% quaternary ammonium salt solution at 25°C for 12 hours, taken out and placed in a constant temperature oven for drying, set The ramie fiber was dried at 60°C to a moisture content of 30wt%, and then added to the hopper of a steam explosion machine, subjected to dispersed steam explosion treatment for 3 times, each steam explosion pressure was 5MPa, and then washed several times with a 50wt% quaternary ammonium salt solution, and placed in an oven at 80°C for 24h to obtain a quaternary ammonium salt coated ramie fiber 1, wherein the quaternary ammonium salt in the quaternary ammonium salt solution used was didecyldimethylammonium bromide, and was a quaternary ammonium salt solution with a quaternary ammonium salt content of 50wt% prepared by YMA-1026 of Shanghai Yuanmu Biotechnology Co., Ltd.);
[0051] Quaternary ammonium salt coated hemp fiber 2: average diameter 30 μm, average length 3.6 mm, quaternary ammonium salt weight percentage 19%, the preparation method thereof is different from that of quaternary ammonium salt coated hemp fiber 1 in that the number of dispersed steam explosion treatments is 2;
[0052] Quaternary ammonium salt coated hemp fiber 3: average diameter 50 μm, average length 3.7 mm, quaternary ammonium salt weight percentage 14%, the preparation method thereof is different from that of quaternary ammonium salt coated hemp fiber 1 in that the number of dispersed steam explosion treatments is 1;
[0053] Quaternary ammonium salt coated hemp fiber 4: average diameter of 160 μm, average length of 4 mm, quaternary ammonium salt weight percentage of 11%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt coated hemp fiber 1 is that the number of dispersed steam explosion treatments is 0 times, and the specific preparation method is as follows: commercially available bundled ramie long fibers with an average diameter of 200 μm are uniformly cut into 4 mm long short fibers, then placed in a 2wt% NaOH solution and soaked at 25°C for 8 hours, washed with clean water several times to remove the residual sodium hydroxide, and the washed short fibers are placed in a 50wt% quaternary ammonium salt solution and soaked at 25°C for 12 hours, taken out and placed in a constant temperature oven for drying, the temperature is set at 60°C, and dried to a moisture content of 30wt%, and then washed several times with a 50wt% quaternary ammonium salt solution, and placed in an oven at 80°C for drying for 24 hours to obtain the treated quaternary ammonium salt coated hemp fiber 4, wherein the quaternary ammonium salt in the quaternary ammonium salt solution used is didecyldimethylammonium bromide;
[0054] Quaternary ammonium salt coated hemp fiber 5: average diameter 14 μm, average length 1.5 mm, quaternary ammonium salt weight percentage 35%, the preparation method thereof is different from that of quaternary ammonium salt coated hemp fiber 1 in that the number of dispersed steam explosions is 5;
[0055] Quaternary ammonium salt coated hemp fiber 6: average diameter 90 μm, average length 3.8 mm, quaternary ammonium salt weight percentage 12%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt coated hemp fiber 6 is that the steam explosion pressure is different, and each steam explosion pressure is 0.5 MPa;
[0056] Quaternary ammonium salt coated hemp fiber 7: average diameter 15 μm, average length 2.1 mm, quaternary ammonium salt weight percentage 28%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt coated hemp fiber 7 is that the steam explosion pressure is different, and each steam explosion pressure is 10 MPa;
[0057] Quaternary ammonium salt coated hemp fiber 8: average diameter of 15 μm, average length of 3.5 mm, quaternary ammonium salt weight percentage of 24%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt in the quaternary ammonium salt solution is didecyldimethylammonium chloride, and the quaternary ammonium salt solution with a quaternary ammonium salt content of 50 wt% is prepared from D1021 (active ingredient content 80 wt%) of Jiangsu Youlixin Chemical;
[0058] Quaternary ammonium salt coated hemp fiber 9: average diameter 15 μm, average length 3.5 mm, quaternary ammonium salt weight percentage 10%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt solution has a quaternary ammonium salt content of 30 wt%, and the immersion time in the quaternary ammonium salt solution at 25° C. is 6 h;
[0059] Quaternary ammonium salt coated hemp fiber 10: average diameter of 15 μm, average length of 3.5 mm, quaternary ammonium salt weight percentage of 50%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt solution has a quaternary ammonium salt content of 60 wt%, and the immersion time in the quaternary ammonium salt solution at 25° C. is 48 h;
[0060] Quaternary ammonium salt coated hemp fiber 11: average diameter of 15 μm, average length of 3.5 mm, quaternary ammonium salt weight percentage of 30%, the difference between the preparation method of the quaternary ammonium salt coated hemp fiber 1 and the quaternary ammonium salt solution of quaternary ammonium salt content of 50wt%, the immersion time in the quaternary ammonium salt solution at 25° C. is 24 h;
[0061] Quaternary ammonium salt coated hemp fiber 12: average diameter of 15 μm, average length of 3.6 mm, quaternary ammonium salt weight percentage of 30%, the preparation method is as follows: commercially available bundled ramie long fiber with an average diameter of 200 μm is evenly cut into 4 mm long short fibers, then placed in a 2wt% NaOH solution at 25°C for 8 hours, washed with clean water several times to remove the residual sodium hydroxide, the washed short fibers are placed in a 50wt% quaternary ammonium salt solution at 25°C for 2 hours, taken out and placed in a constant temperature oven for drying, set The ramie fiber was dried at 60°C to a moisture content of 30wt%, and then added to the hopper of a steam explosion machine, subjected to dispersed steam explosion treatment 3 times, each steam explosion pressure was 5MPa, and then washed several times with a 50wt% quaternary ammonium salt solution, and placed in an oven at 80°C for 24h to obtain a quaternary ammonium salt coated ramie fiber 12, wherein the quaternary ammonium salt in the quaternary ammonium salt solution used was didecyldimethylammonium bromide, and was a quaternary ammonium salt solution with a quaternary ammonium salt content of 50wt% prepared by YMA-1026 of Shanghai Yuanmu Biotechnology Co., Ltd.)
[0062] Hemp fiber 13: average diameter of 15 μm, average length of 3.5 mm, quaternary ammonium salt weight percentage of 0, the preparation method is as follows: commercially available bundled ramie long fibers with an average diameter of 200 μm are evenly cut into 4 mm long short fibers, then immersed in a 2wt% NaOH solution for 8 hours, washed with clean water several times to remove the residual sodium hydroxide, and then placed in a constant temperature oven for drying, the temperature is set at 60°C, dried to a moisture content of 30wt%, and then added to the hopper of a steam blasting machine, subjected to dispersed steam explosion treatment 3 times, each steam explosion pressure is 5MPa, then washed with water several times, placed in an oven at 80°C for drying for 24 hours, to obtain hemp fiber 13;
[0063] Compatibilizer 1: Ethylene-vinyl acetate copolymer grafted with maleic anhydride, EVA-g-MAH, manufactured by Dow Chemical, USA, brand C250;
[0064] Compatibilizer 2: Ethylene-ethyl acrylate copolymer grafted with maleic anhydride, EEA-g-MAH, model is French Arkema, manufacturer is Lotader3210;
[0065] Hypophosphite flame retardant 1: aluminum hypophosphite, commercially available;
[0066] Hypophosphite flame retardant 2: divinyl aluminum hypophosphite, commercially available;
[0067] Antioxidant: Antioxidant 1010, commercially available;
[0068] Lubricant: EBS (N,N-ethylenebisstearamide), commercially available.
[0069] Each of the following embodiments and comparative examples provides a polyolefin material, comprising the following steps: mixing all the raw materials, melt extruding, granulating, and drying to obtain the polyolefin material; wherein the screw aspect ratio of the twin-screw extruder is (36-52):1, and the temperature of each zone of the twin-screw extruder is preferably set as follows: 80-120°C in zone 1, 180-200°C in zones 2-5, and 190-230°C in zones 6-8. The formulas of the polyolefin materials of these embodiments and comparative examples are shown in Tables 1 and 2.
[0070] The following performance tests were performed on the polyolefin materials of the above embodiments and comparative examples. The test results are shown in Tables 1 and 2:
[0071] (1) Flexural modulus test: Test the flexural modulus of materials according to ISO 178-2010 standard;
[0072] (2) Anti-bite test: Three flat plastic plates with a length of 1000 mm, a width of 500 mm, and a wall thickness of 5 mm were extruded and laid on the surface of the cement slatted floor in the pig fattening house, with a total area of 15,000 cm 2; The fattening pig house has 10 pigs and the test period is set to 14 days. Then the area of the pigs biting and the biting depth are measured, calculated and counted;
[0073] (3) Antibacterial rate test: Prepare 100*100*2 mm plastic samples and test the antibacterial rate according to ISO 22196-2011;
[0074] (4) Vertical burning test: According to the UL94-2022 standard, the thickness of the test specimen is 3.2 mm, and the flame burning time after two combustions is recorded, which are t1 and t2 respectively. There are 5 specimens in each group, and the total flame burning time of these 5 specimens is t1+t2;
[0075] Table 1
[0076]
[0077]
[0078] Note: The amount of didecyldimethylammonium bromide used in Comparative Example 2 shown in Table 1 is the amount of pure didecyldimethylammonium bromide. The didecyldimethylammonium bromide raw material used in Comparative Example 2 is analytical grade and the manufacturer is Yixing Kailida Chemical Co., Ltd.
[0079] Table 3
[0080]
[0081]
[0082] From the above data, it can be seen that the compositions of each embodiment have good mechanical properties, anti-bite properties, antibacterial properties and flame retardancy, such as a bending modulus of more than 1200 MPa and a biting area of 1950 cm 2 The biting depth was below 3 mm, the antibacterial rate was above 70%, and the sum of t1+t2 of 5 specimens was below 47 s.
[0083] Comparative Example 1 did not use quaternary ammonium salt, resulting in deviations in the mechanical properties, anti-bite properties and antibacterial properties of the material; Comparative Example 2 physically mixed the quaternary ammonium salt with the hemp fiber without coating modification, resulting in deviations in the mechanical properties, anti-bite properties and antibacterial properties of the material.
[0084] By comparing Examples 1 to 12 with Comparative Examples 1-2, it can be seen that the quaternary ammonium salt content in the quaternary ammonium salt-coated hemp fiber will affect the mechanical properties, anti-bite properties and other properties of the composition. Preferably, the quaternary ammonium salt content in the quaternary ammonium salt-coated hemp fiber is 23% to 31% to make the mechanical properties and anti-bite properties of the material better.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A polyolefin material, characterized in that: Contains the following components in parts by weight:
2. The polyolefin material according to claim 1, characterized in that The weight percentage of the quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber is 9% to 51%.
3. The polyolefin material according to claim 2, characterized in that The weight percentage of the quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber is 23% to 31%.
4. The polyolefin material according to claim 1, characterized in that The average length of the bast fibers in the quaternary ammonium salt-coated bast fibers is ≥1 mm, and the average diameter is ≤100 μm.
5. The polyolefin material according to claim 4, characterized in that The average length of the quaternary ammonium salt coated hemp fiber is 1 to 4 mm, and the average diameter of the quaternary ammonium salt coated hemp fiber is 5 to 95 μm.
6. The polyolefin material according to claim 1, characterized in that The preparation method of the quaternary ammonium salt-coated hemp fiber comprises soaking the hemp fiber in an alkali solution, washing with water and performing a steam explosion treatment.
7. The polyolefin material according to claim 1, characterized in that The quaternary ammonium salt in the quaternary ammonium salt coated hemp fiber includes at least one of didecyl dimethyl ammonium bromide, didecyl dimethyl ammonium chloride, dioctyl dimethyl ammonium bromide and dioctyl dimethyl ammonium chloride.
8. The polyolefin material according to claim 1, characterized in that At least one of the following conditions (1) to (6) is also met: (1) The hemp fiber in the quaternary ammonium salt-coated hemp fiber includes at least one of ramie fiber, flax fiber and sisal fiber; (2) The method for preparing the quaternary ammonium salt coated hemp fiber comprises soaking or ultrasonically treating the hemp fiber with a quaternary ammonium salt solution; (3) The polyolefin resin includes at least one of high-density polyethylene, low-density polyethylene, linear low-density polyethylene, and polypropylene; (4) The compatibilizer comprises a polar monomer graft polymer, wherein the polymer comprises at least one of ethylene-vinyl acetate copolymer and ethylene-ethyl acrylate copolymer, and the polar monomer comprises maleic anhydride or its derivatives; (5) The hypophosphite includes a hypophosphite flame retardant, and the hypophosphite flame retardant includes at least one of aluminum hypophosphite and divinyl aluminum hypophosphite; (6) The invention also includes the following components by weight: 0.1-1 part of antioxidant and 0.1-1 part of lubricant.
9. A method for preparing a polyolefin material according to any one of claims 1 to 8, characterized in that: The following steps are involved: All the raw materials are mixed, melt-extruded, granulated, and dried to obtain a polyolefin material.
10. Use of the polyolefin material according to any one of claims 1 to 8 in animal breeding facilities.
Citation Information
Patent Citations
Flame-retardant bast fiber-plastic composite material, and preparation method thereof
CN103937066A
High-modulus halogen-free flame-retardant jute fiber reinforced polypropylene composite material and preparation method thereof
CN115873344A
Preparation method of washable antibacterial nylon composite fabric
CN117721560A
Polyolefin composition as well as preparation method and application thereof
CN118290853A
Method of producing nanocellulose
US20170306055A1